Koji Starter and Koji World in Japan - Yamashita, Hideyuki (J Fungi (Basel), 2021)
Koji is made by culturing koji mold on grains. Koji has wide-ranging applications, for example, in alcoholic beverages and seasonings. The word ‘mold’ generally has a bad image, but in Japan, koji mold is valued for its usefulness, and over the years, efforts have been made to make safe, stable, and delicious food products from it. Koji mold spores, essential when making koji, are called koji starter in the industry. From the many available strains, those suitable for the production of each fermented food are chosen based on indicators such as growth rate and enzyme production capacity. In manufacturing using microorganisms, purity and yield are prioritized. However, the production of fermented foods using koji is more complex, with focus not only on the degree of decomposition of raw materials but also on factors influencing overall product design, including palatability, color, smell, and texture. Production can be facilitated by the variety of koji brought about by the diversity of koji mold combined with the solid culture method which increases the amount of enzyme production. In this report, we introduce the history of koji starter in Japan, the characteristics of koji mold in practice, and various fermented foods made from it. In addition, the factors affecting the quality of koji in solid culture are described.